Schaum's outline introduction to mathematical economics - Dowling, Edward T. (New York : McGraw Hill Education, 2012)
'Schaum's Outlines' present all the essential course information in an easy-to-follow, topic-by-topic format. You also get hundreds of examples, solved problems, and practice exercises to test your skills.